Structure and characterization of ruled surfaces in Minkowski 3-space. Issue 2 (2nd July 2016) - Güler, Fatma; Kasap, Emîn
Abstract: In this paper, we consider non developable ruled surface with spacelike ruling, timelike ruling, respectively. We give the relations between the structure functions with the curvature and torsion of the striction line of the timelike and spacelike non developable ruled surfaces. Also, we have calculated the gaussian and mean curvatures of timelike and spacelike non developable ruled surfaces using the structure functions.